Ancaman Keamanan Siber dan Peran Aktor Non-Negara di Dunia Digital - Serly Sintia Saramuke; Vianna Antoneta Putri; Agnes Marianti Sormin; Muthia Nugraha (Syntax Idea)
Along with the rapid advancement of digital technology and tnternet where the global community is highly dependent on technology and imternet, the whole world is faced with very serious challenges in the form of cyber crime. These challenges not only require the role of state actors in dealing with them, but non-state actors also play an important role. Therefore, this article aims to identify what forms of cybersecurity threats are faced today and analyze the role of non-state actors in dealing with cyber security threats. This article uses a qualitative approach with a literature study method to analyze cyber threats and the role of non-state actors in dealing with them through non-numerical data from reliable written source. The results show that cyber security threats are increasing along with the growth of global internet users which include various types such as cyber crime, cyber warfare, and cyber terrorism, which are further exacerbated by the COVID-19 pandemic. In dealing with these threats, non-state actors such as international organizations, technology companies, and non-governmental organizations play an important role in public education, cooperation between countries, and strengthening cyber policies and defenses, especially through social media as an effective communication channel.